2010
DOI: 10.1007/s00122-010-1336-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cytoplasm types in rapeseed (Brassica napus L.) accessions by a multiplex PCR assay

Abstract: Cytoplasmic male sterility (CMS) has widely been used as an efficient pollination control system in rapeseed hybrid production. Identification of cytoplasm type of rapeseed accessions is becoming the most important basic work for hybrid-rapeseed breeding. In this study, we report a simple multiplex PCR method to distinguish the existing common cytoplasm resources, Pol, Nap, Cam, Ogu and Ogu-NWSUAF cytoplasm, in rapeseed. Cytoplasm type of 35 F(1) hybrids and 140 rapeseed open pollinated varieties or breeding l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 22 publications
1
15
0
6
Order By: Relevance
“…, Zhao et al. ) in the present study. As expected, a specific amplification product of about 465 bp was yielded in RF04(R), which was specific for orf138 ( ogu CMS type), 1102 bp in Westar, which was specific for orf222 ( nap CMS type), and 747 bp in Zhong 9A, which was specific for orf224 ( pol CMS type).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…, Zhao et al. ) in the present study. As expected, a specific amplification product of about 465 bp was yielded in RF04(R), which was specific for orf138 ( ogu CMS type), 1102 bp in Westar, which was specific for orf222 ( nap CMS type), and 747 bp in Zhong 9A, which was specific for orf224 ( pol CMS type).…”
Section: Resultsmentioning
confidence: 96%
“…The result of multiplex PCR (Zhao et al. ) and molecular cloning and sequencing of the specific PCR bands revealed that the cytoplasm of this male sterile accession was identical to that of nap CMS. Together, this male sterile accession belonged to the nap CMS type, and its fertility was controlled by a pair of genic recessive genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several CMS systems as Ogu-INRA, MSL and Pol are already used in hybrid breeding of Brassica napus and commercial cultivars based on Ogu-INRA, MSL and Safecross MS are registered and cultivated in the Czech Republic. In China, 70% rapeseed cultivars are based on CMS, mainly the Pol or Shaan 2A systems that both arose spontaneously within the species (Zhao et al 2010). The orf224-1 gene has been isolated as a Shaan 2A CMS-associated gene (Wang et al 2002).…”
mentioning
confidence: 99%
“…Genomic DNA was isolated according to CTAB procedure described by Doyle and Doyle (1987). Total gDNA has been used for PCR because it has already been confirmed that gDNA is mixed with mtDNA and PCR amplification of mtDNA orf genes is possible (Zhao et al 2010). The concentration and quality of DNA was determined with a BioMate 5 spectrophotometer.…”
mentioning
confidence: 99%